Realizing Religious Moderation Through Al-Qur'an Education Park at Nurul Yaqin Mosque, Kebon Melati Village, Tanah Abang District - Rina Septiani; Ummi Kulsum; Susanto Susanto (Jurma : Jurnal Program Mahasiswa Kreatif, 2022)
The radicalism of terrorism in Indonesia is increasingly seen as dangerous. The incident of self-bombing in a Christian house of worship in 2018 in East Java involving four children who were still at school is clear evidence of the resurgence of terrorism. The highlight is that the child was still at the primary stratum level. This service has the aim of participating in solving this problem using a form of service too early Islamic education forums, namely the Al-Qur'an Education Park (TPA) using the theory of religious moderation as a basis. The program on the agenda is teaching and learning activities at the TPA. With the Participatory Action Research (PAR) method lasting for one month, namely February to March 2020, the activity concludes that the activities carried out can create a moderate religious understanding of TPA residents, or at the very least, can strengthen religious moderation. Raising awareness that loving the motherland is a must and an obligation as enlightenment regarding acts of radicalism and terrorism is a heinous thing. Apart from this, the servant is aware that there is much that must be done in making changes toward moderation.